Performance evaluation of a common effluent treatment plant for tannery industries - Vasudevan, N; S, Justin Aaron P; Greeshma, O (Journal of Ecobiotechnology, 2012)
Tannery is one of the oldest industries in the world and is one of the fastest developing industries in India. It is one of the problematic industries in India which generate high quantum of wastewater with high TDS and toxicity due to chromium. Hence, discharge of tannery effluent is a very serious issue. Many conventional treatment processes has been carried out in these industry before the discharge of effluent. One of the most common treatment process applied is biological treatment process by activated sludge process and upflow anaerobic sludge blanket process. Due to the high cost of installation for this treatment process, in many of the small scale tannery industries in India, the wastewater treatment is carried out in common effluent treatment plant (CETP). In the present study the performance of CETP for tannery effluent in terms of Biological oxygen demand (BOD), Chemical oxygen demand (COD), Total suspended solids (TSS), Total dissolved solids (TDS), and by water tracer studies using Rhodamine. ETP showed a removal efficiency of BOD-66%, COD- 21%, TSS-21% and TDS-5%. The study revealed that ETP has to be redesigned based on the characteristics of influent wastewater in order to meet the Pollution Control Board prescribed standard limits for ETP.